The Effect of Voice Record (Murottal) of Surah Ar-Rad Verses 1-28 with Video on Elderly Anxiety Level in RW 02 Batursari Village in Covid-19 Times - Zulfatul Asfiyah; Suci Ratna Estria (Proceedings Series on Health & Medical Sciences, 2021)
World Health Organization declared covid-19 as the sixth public health emergency that required global attention. The Covid-19 pandemic caused the risk of complications which was higher in some vulnerable populations including the elderly. Moreover, Covid-19 prevention such as self-isolation and quarantine affected community activities as well as causing psychosocial problems, one of which was anxiety. Some anxiety treatments could be conducted using distraction techniques, deep breathing, and music therapy including murottal Al Qur’an. To figure out the effect of the medium of murottal of Surah Ar-Rad verses 1-28 with video as the media on the elderly anxiety level in rw 02 Batursari village in Covid-19 times. The study used a pre-experimental design with one group pretest and posttest design. Measurement of research variables was carried out before and after giving the medium of the video to the elderly who experienced anxiety. The samples were 41 respondents who were selected using the purposive sampling technique. The results showed that the average age of the respondents was 64 years, with an average value of anxiety level before the medium of 10.14 and after the medium, the average value of the respondent's anxiety level decreased to 3.65 or decreased by 6.49. Based on the Mann-Whitney test, the results obtained a Z value of -7.897 and a significance value of 0.001 (p 0.05) with an effect size of 1.23. Therefore, there was the effect of the medium of murottal of surah Ar-Rad verses 1-28 with video on the elderly anxiety level in RW 02 Batursari village during in Covid-19 times. There is an effect of the medium of murottal of surah Ar-Rad verses 1-28 with video on the elderly anxiety level in rw 02 Batursari village during in Covid-19 times.